Ethers - DeRosa, Thomas F (Advances in Synthetic Organic Chemistry and Methods Reported in US Patents, 2006)
Ethers are a class of organic compounds that contain an ether group—an oxygen atom connected to two alkyl or aryl groups. This chapter focuses on ethers. A US patent related to the subject discussed is used, details related to the patent are provided, and some other valuable information is mentioned for a better understanding of the subject. This chapter covers three chapterd. The first one is diaryl ether condensation reactions. The assignee of this patent is Massachusetts Institute of Technology and the utility designation is aromatic ether coupling reagent. The second patent is preparation and use of ionic liquids in microwave-assisted chemical transformations. The assignee is Personal Chemistry I Uppsala AB and the utility designation is high yielding alkylations using ionic solvents. The third patent is wurster's crown ligands. The assignee is East Carolina University and the utility designation is liquid crystal displays. The chapter also discusses various reactions related to the topic, derivatives, experimental details, notes, and references to other US patents.